Brand Trust Mediates E-Wom And Brand Equity Toward Customer Loyalty on Shopee - Ananda, Nadya Asri; Nora, Liza (LP2M IAIN Palopo, 2025)
This study aims to examine the influence of Electronic Word of Mouth and Brand Equity on Customer Loyalty, with Brand Trust as a mediating variable, in the context of Shopee Indonesia’s e-commerce platform. The research adopts a quantitative approach using a structured survey distributed to active Tiktok and Shopee users. Data were analyzed using the Structural Equation Modeling method with a Partial Least Squares approach. The results show that both Electronic Word of Mouth and Brand Equity have a positive influence on Customer Loyalty. Electronic Word of Mouth also has a significant impact on Brand Trust, while Brand Equity does not. Furthermore, Brand Trust directly influences Customer Loyalty and mediates the relationship between Electronic Word of Mouth and Customer Loyalty, but not between Brand Equity and Customer Loyalty. These findings underscore the importance of trust-building and consumer engagement in digital marketplaces. This research contributes to the field by providing empirical insights into the interplay between consumer perception, trust, and loyalty in the growing landscape of digital commerce.